Little-Parks oscillations in an insulator - Kopnov, G. (2013)
We present the results of a magnetoresistance study of the disorder-induced superconductor-insulator transition in an amorphous indium-oxide thin film patterned by a nanoscale periodic array of holes. We observed Little-Parks-like oscillations over our entire range of disorder spanning the transition. The period of oscillations was unchanged and corresponded to the superconducting flux quantum in the superconducting as well as in the insulating phases. Our results provide direct evidence for electron pairing in the insulator bordering with superconductivity.